Problem Analysis Of Solair Incinerator Using Intergration Analysis Of Product Decomposition And Modularization With Contact And Channel Model (c&cm) Approach As A Reference For Designing The Improvement Of Product Architecture - Kartika Andini Putri; Rino Andias Anugraha; Muhammad Iqbal (eProceedings of Engineering, 2015)
Abstract System engineering of product requires tools and technique for system decomposition and integration to simplify the complex interactions. Otherwise most of the modularization methods focus on the redesign of existing products, in such matrix representation is often used as a tool for integration analysis. This paper focus on component based system architecture and implements effective method for supporting inexperience designer to analyze the problem of product architecture using â€œContact & Channel Modelâ€ that developed at the University Karlshruhe. Bandung Techno Park, Telkom University developed custom design of incinerator named SOLAIR as an alternative technologies to solve domestic waste problem. From the interview and observation, the authors found some weaknesses that occur such as difficulties way to repair some components because the design is integral and some of components placed adjacent to burner that impact higher risk of failure. This paper lead to conclusions regarding problem analysis of SOLAIR incinerator using Faiure Mode Effect Analysis (FMEA) that resulted RPN value for suggestion in future research and problem analysis of incinerator using integration analysis that resulted six clustered (Fuel, Burning, Waste, Cooling, Waste mixer, and Disposal chunks) based on component interactions. Conduncting with Modularization with C&CM approach that analyze functions involving in each module and detachability of each connecting surface of the modules (WSs of WSP 1, 2, 11,and 12 has to be concerned for product architecture improvement in future research. Keywords: Product Architecture, Modularization , Integration Analysis , Incinerator